Locally Available Natural Dyes for Dyesensitized Solar Cells - Karmakar, S; Zaman, Q M Arman Uz; Hossain, M S; Siddika, A; Tabassum, S; Ibrahim, A S M; Huque, S (Dhaka University Journal of Applied Science and Engineering, 2023)
Different types of natural dyes are commonly used to fabricate dyesensitized solar cells which are cheaper, simpler, and environmentally friendlier than conventional crystalline silicon solar cells. This paper objectifies the performance of locally grown natural dyes from Dhaka, Bangladesh using a simple fabrication design. Four natural dyes were obtained separately from spinach, turmeric, pomegranate, and beetroot which contain chlorophyll, curcumin, anthocyanin, and betanin pigments respectively. Ultraviolet-visible spectroscopy illustrated the optical properties of these dyes diluted in ethanol. Spinach and turmeric extracts showed sharper absorption peaks which qualify them as better sensitizers than pomegranate and beetroot extracts. Photoanodes (of thickness 15-20 μm) were prepared by employing the doctor blade technique on fluorine-doped tin oxides using TiO2 nanoparticles of anatase form and graphite coated fluorine-doped tin oxides were used as counter electrodes. The photoelectric measurements of the fabricated cells were done under air mass (AM) 1.5 and power density of 100 mW/cm2. The fabricated cell of turmeric extracted dye showed the highest efficiency of 0.031% (Open circuit voltage, VOC = 380 mV, Short circuit current density, JSC = 0.234 mA/cm2) and the cell using beetroot extract gave the highest fill factor (FF) of about 50% among the prepared dyesensitized solar cells. DUJASE Vol. 7(1) 38-44, 2022 (January)